Nitrogen diffusion in nitrogen-doped yttria stabilised zirconia - Kilo, Martin (2004)
Nitrogen self-diffusion was measured in single crystalline nitrogen-doped yttria-stabilised zirconia (YZrON) containing 10 mol% yttrium oxide. Samples containing two different nitrogen contents (5 and 6 mol% N on the anion sublattice) were investigated as a function of temperature (650–1000 K) using implanted 15N as a stable tracer. For a given temperature, the nitrogen diffusivity was nearly independent of the nitrogen content in the nitrogen-doped yttria-stabilised zirconia, which can be only partially understood using defect chemistry. The activation enthalpy of nitrogen diffusion was between 2 and 2.5 eV with a preexponential factor of the order of 100 cm2 s−1, which corresponds to a migration entropy of 5 kB. The surface exchange reaction between nitrogen and the oxonitride surface was investigated at 1073 K using 200 mbar gaseous 15N2 and was found to be slow but considerable. Decreasing the oxygen content in the gas phase can enhance the nitrogen incorporation into the oxonitrides.